2022
DOI: 10.1088/1741-4326/ac5448
|View full text |Cite
|
Sign up to set email alerts
|

NSTX-U theory, modeling and analysis results

Abstract: The mission of the low aspect ratio spherical tokamak NSTX-U is to advance the physics basis and technical solutions required for optimizing the configuration of next-step steady-state tokamak fusion devices. NSTX-U will ultimately operate at up to 2 MA of plasma current and 1 T toroidal field on axis for 5 seconds, and has available up to 15 MW of Neutral Beam Injection (NBI) power at different tangency radii and 6 MW of High Harmonic Fast Wave (HHFW) heating. With these capabilities NSTX-U will develop the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 151 publications
0
5
0
Order By: Relevance
“…Being limited to low-k HHFW heating regimes, there is little or no danger that this type of resonant surface wave excitation on filaments will pose a problem for future tokamaks such as ITER, or even NSTX-U, which will operate at double the magnetic field strength of NSTX [56]. where φ s is the phasing of strap s. The straps are connected in pairs such that φ s+6 = φ s + π [57].…”
Section: Discussionmentioning
confidence: 99%
“…Being limited to low-k HHFW heating regimes, there is little or no danger that this type of resonant surface wave excitation on filaments will pose a problem for future tokamaks such as ITER, or even NSTX-U, which will operate at double the magnetic field strength of NSTX [56]. where φ s is the phasing of strap s. The straps are connected in pairs such that φ s+6 = φ s + π [57].…”
Section: Discussionmentioning
confidence: 99%
“…When the temperature gradient a/L T0 is increased by 20%, the growth rates at all scales are also increased by approximately 20%. Note that it is also observed in other machines such as NSTX [7], DIII-D [16], JET [30], etc, that ETG turbulence is sensitive to temperature gradient. The temperature gradient sensitivity The On the Growth rate spectrum at ρtor = 0.94 during the pre-ELM stage.…”
Section: Local Pre-elm Simulationsmentioning
confidence: 60%
“…It has been noted that both the peeling-ballooning and KBM calculations become more challenging at low aspect ratio, due to strong coupling of poloidal modes, and highly shaped geometry [22]. Kinetic ballooning mode calculations in low aspect ratio devices, using both gyrokinetic and high-n MHD proxy calculations, have previously found that fully developed pedestals in these devices are typically near KBM criticality [22,[36][37][38], though in some cases non-local effects need to be accounted for [39]. Similarly, ELM onset is observed to occur near predicted peeling-ballooning mode onset, though in some cases with a lower growth rate threshold than would be expected due to diamagnetic stabilization, with the importance of resistive effects hypothesized as a possible cause [40].…”
Section: Equilibrium Reconstruction and Pedestal Stability Analysismentioning
confidence: 99%